The effect Of Using Three Teaching Styles On The level and Frequency of Performing Forehand and backhand Shot In Tennis - Nagmeldin, Eman; Hussein, Loai (Journal of Physical Education, 2008)
The study aimed at studying the effect of using three teaching styles in physical education (Empirical, Practical and self evaluation of performance) on the level of performing forehand and backhand shot in tennis. In addition to that the study aimed at making a comparison between the three teaching methods understudy on the level and frequency of performing forehand and backhand shot in tennis. The problem of the study lies in not using other methods for teaching save the traditional method. The researcher hypothesized that there are no statistical differences between pre and posttests in forehand and backhand shot in tennis among the three teaching methods. Also they hypothesized that there are no statistical differences in the level of performing forehand and backhand shots in tennis after applying three teaching methods. The researchers used the experimental method. The subjects were (42) third year students of the college of physical education/ University of Slemania. The subjects were divided into three teaching groups. Three teaching methods were used; empirical, practical and self evaluation method. The pre tests were conducted then followed by the teaching method ending in the posttests. The researchers used many statistical operations to treat the results like t tests, standard deviation and mean. The results showed that using three methods of teaching have a positive effect on learning forehand and backhand shot in tennis. Also when comparing between the teaching methods it appeared that the practical method is the best in teaching forehand and backhand shot in tennis. In addition to that the results showed that the frequency of performance was positive indicator for high achievement. Finally all teaching methods can be used for developing the level of students while learning forehand and backhand shot. The researchers then recommended using the teaching methods understudy for teaching forehand and backhand shot in tennis and making similar studies on other groups and other teaching methods.